Effects of 20-hydroxyecdysone on the development and morphology of the red fl our beetle, Tribolium castaneum (Coleoptera: Tenebrionidae) - Nujira Tatun (2018)
© Institute of Entomology, Biology Centre, Czech Academy of Sciences, České Budějovice. The red fl our beetle, Tribolium castaneum, is a pest of stored products. It is also regarded as a model species for studying development, genetics, biology, physiology and biochemistry. Recently, it has become a model for use in RNA interference experiments. 20-hydroxyecdysone (20E) is involved in insect metamorphosis and its role in organ development in T. castaneum are based on hormonal treatment in conjunction with RNAi. However, information on the biological, morphological and physiological effects of 20E on T. castaneum is still limited. This study reveals the responses of T. castaneum larvae to injections with various doses of 20E (100, 200, 300, 400 and 500 ng / insect). The results show that larvae injected with 20E reached the prepupal, pupal and adult stages earlier than the control group. Different degrees of morphological change were observed in nine traits, including the appearance of pupal prothetelic organs in the larvae. Moreover, an injection of a high dose of 20E reduced the body weights of the resulting insects at each stage, as well as the length and width of elytra. The enzymatic activity of a-amylase in the resulting adults also decreased signifi cantly. This indicates that injection of 20E caused precocious metamorphosis in T. castaneum by inducing changes in morphology and a-amylase activity, and the optimal concentrations that induce such phenomena were in the range of 100-200 ng / insect. Further investigations are needed to examine the roles of 20E in the regulation of a-amylase in T. castaneum.